Electrochemical, high-resolution photoemission spectroscopy and vdW-DFT study of the thermal stability of benzenethiol and benzeneselenol monolayers on Au(111) - Cometto, F P (Langmuir : the ACS journal of surfaces and colloids, 2012)
The preparation and thermal stability of benzenethiol and benzeneselenol self-assembled monolayers (SAMs) grown on Au(111) have been investigated by electrochemical experiments and high-resolution photoemission spectroscopy. Both techniques confirm the formation of monolayers with high packing densities (θ = 0.27-0.29 ML) and good degrees of order in both cases. Despite many similarities between the two SAMs, the thermal desorption is distinctly different: whereas the benzenethiol SAM desorbs in a single steplike process, the desorption of the benzeneselenol SAM occurs with a much lower activation energy and involves the cleavage of some Se-C bonds and a change in molecular configuration from standing up to lying down. This behavior is explained by considering the different nature of the bonding of the headgroup with the metal surface and with the phenyl ring. Density functional theory calculations show that the breakage of the Se-C bond has a lower activation energy barrier than the breakage of the S-C bond